2009
DOI: 10.1007/s00586-009-1203-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and clinical outcome of screw placement in adolescent idiopathic scoliosis: evaluation with low-dose computed tomography

Abstract: Posterior corrective surgery using ''all pedicle screw construct'' carries risk of neurovascular complications. The study aims were to assess the screw placement in patients with adolescent idiopathic scoliosis using CT with low-radiation dose, and to evaluate the clinical outcome in patients with misplaced pedicle screws. CTs of 49 consecutive patients (873 screws, 79% thoracic) were retrospectively evaluated by two independent radiologists. A new grading system was developed to distinguish between lateral, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 22 publications
9
27
0
7
Order By: Relevance
“…The Values are presented with standard deviation method does not require additional examination to assess the axial plane, and vertebral axial rotations, in particular, can be assessed accurately in routine pre-and postoperative clinical use with greatly reduced exposure to ionizing radiation [12]. As a matter of fact, the mean effective dose calculated in the current study was 6 times lower than the one reported by Abul-Kasim [24,27] with low-dose CT. The device is expensive, but the cost of an examination remains the same as the one of a conventional full spine radiograph in our institution.…”
Section: Low Dose Biplanar Stereoradiographymentioning
confidence: 56%
“…The Values are presented with standard deviation method does not require additional examination to assess the axial plane, and vertebral axial rotations, in particular, can be assessed accurately in routine pre-and postoperative clinical use with greatly reduced exposure to ionizing radiation [12]. As a matter of fact, the mean effective dose calculated in the current study was 6 times lower than the one reported by Abul-Kasim [24,27] with low-dose CT. The device is expensive, but the cost of an examination remains the same as the one of a conventional full spine radiograph in our institution.…”
Section: Low Dose Biplanar Stereoradiographymentioning
confidence: 56%
“…Prior series have reported complication rates using pedicle screw constructs, but most have revolved around placement of screws and not the clinical complications [32][33][34]. Our series only had three malpositioned screws, but these were not evaluated by post-operative CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) scan has also been used for preoperative measurement and postoperative assessment in spine surgery [11,12]. With advances in equipment and scanning parameter settings, single-dose radiation has reached an acceptable range [13].…”
Section: Introductionmentioning
confidence: 99%